Three species of the millipede family Platyrhacidae from Costa Rica: a new Barydesmus Cook, 1896 and two oldest Nyssodesmus Cook, 1896 (Diplopoda, Polydesmida) - Golovatch, Sergei I.; Korotayeva, Alyona M.; Martínez-Torres, Daniela (Zootaxa, 2024)
Three species of Platyrhacidae from Costa Rica are treated and illustrated in due detail: Barydesmus truncatus sp. nov., Nyssodesmus alboalatus Cook, 1896, and N. python (Peters, 1865). Barydesmus truncatus sp. nov. is easily distinguished from congeners mainly through a peculiar, truncated tip of the gonopodal lateral branch. Nyssodesmus python, presently considered as perhaps the most common platyrhacid widespread along the Caribbean coast of Costa Rica, is revised and properly illustrated based both on new and old samples, including the female holotype. In gonopodal structure, only very slightly variable though, N. python is virtually identical to N. alboalatus Cook, 1896, the type species of Nyssodesmus Cook, 1896, also revised and illustrated from type material, including lectotype designation. It could have jeopardized the younger N. alboalatus had it not been for a few morphological differences observed between both these two formal species: usually completely dark mid-dorsal parts of metaterga with contrasting light paraterga and darker legs, distinct metatergal granulations and a missing to vestigial solenomere in N. alboalatus, vs more or less wide, pale, mid-dorsal parts of metaterga with contrasting light paraterga and either light or dark legs, indistinct metatergal granulations and often a very short solenomere vestige in N. python. Coupled with gross sympatry and variable colour patterns, the issue of their synonymy, N. python being the older and therefore valid name, is bound to persist until molecular genetic techniques are applied.